HEARING IMPAIRMENT AND ACCESSING TO INFORMATION SERVICES VIA ONLINE PLATFORM OF MASS MEDIA - Maneehaet , Sirodom; Saitong, Pongpipat (Journal of MCU Nakhondhat, 2023)
The purposes of this research were 1) to study the needs of people with hearing impaired in accessing to information services via online platform of mass media, and 2) to compare the needs of accessing to information services classified by gender, age, year of studying, manner of study attending, domicile, and registration of disabilities, which has used survey research, the research population consisted of 187 hearing impaired people studying in Udon Thani School for the Deaf, and the target group of the research was selected by purposive sampling, 23 people. The research tool was a questionnaire on demand for access to information services via online platform of mass media, divided into 4 aspects: 1) media content, 2) media format via online platform, 3) communication channel and 4) communicator. The statistics used in this research were mean, percentage, standard deviation, and t-test. The results of the research revealed that 1) The hearing impaired people in Udon Thani School for the Deaf had the needs for accessing to information services via online platform of mass media both in overall and in each aspect needs at the high level (Mean = 4.26, S.D. = 0.61), and 2) The hearing impaired people in Udon Thani School for the Deaf with different individual factors include: gender, age, year of studying, manner of study attending, domicile, and registration of disabilities were needs in accessing to information services via online platform of mass media are no different.